1984
DOI: 10.1007/bf01317081
|View full text |Cite
|
Sign up to set email alerts
|

Immunological findings in whole and parotid saliva of patients with Crohn's disease and healthy controls

Abstract: Since oral lesions appear to occur more commonly in patients with Crohn's disease (CD) than in normal controls or patients with ulcerative colitis, it has been suggested that a deficit of locally produced IgA allows the invasion of the oral mucous membrane by antigens and contributes to the production of oral lesions. In connection with this hypothesis, the concentrations of IgA, IgM, and IgG in whole and parotid saliva were investigated by the ELISA technique in 20 patients with CD and 20 healthy subjects mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 5 publications
1
15
0
Order By: Relevance
“…This sug gestion is in agreement with the observation of a generally activated immunoglobulinsynthesizing system in CD in contrast with the local activated system in UC [5][6][7][8]. The relevance of these findings toward the patho genesis of IBD has still to be clarified in studies dealing with intestinal cells and 'spe cific' antigens.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This sug gestion is in agreement with the observation of a generally activated immunoglobulinsynthesizing system in CD in contrast with the local activated system in UC [5][6][7][8]. The relevance of these findings toward the patho genesis of IBD has still to be clarified in studies dealing with intestinal cells and 'spe cific' antigens.…”
Section: Discussionsupporting
confidence: 87%
“…Involvement of the immunoglobulin-syn thesizing system is supported by the in creased numbers of B cells [4] and plasma cells in the lamina propria of the colon in both CD and UC [5,6], Moreover, in CD other parts of the gastrointestinal tract also seem to take part in this process, since macroscopically unaffected buccal mucosa con tained increased numbers of immunoglobu lin-containing plasma cells, while saliva of CD patients had significantly elevated IgA, IgG and IgM levels compared with controls [7,8], The systemic activation of the immu noglobulin synthesis is suggested to be the result of the migration of committed lym phocytes from a site of antigenic stimulation to the mucosal tissue, including the secretory glands. This should be reflected in the in vitro response of (re)circulating lympho cytes.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, non‐specific IgA and IgA2 immunoglobulin levels in whole and parotid saliva are raised in patients with OFG, with or without gut inflammation, suggesting that salivary gland involvement may occur in this disorder. Although a previous study has reported raised salivary IgA in whole saliva in CD [28], no previous studies have compared OFG with and without gut involvment. Serum IgA responses to S. cerevisiae were raised only in those with existing gut disease and thus assay of serum IgA antibody responses may prove useful in indicating concurrent gut disease and possibly progression of OFG to gut involvment.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with IBD may complain of dry mouth, similar to the sicca syndrome observed in transplanted patients under immunosuppressive therapy. Interleukin‐6 changes in saliva of patients with IBD have been reported as well as several abnormal immunological findings in whole and parotid saliva …”
Section: Spectrum Of Oral Manifestations In Ibdmentioning
confidence: 99%